SAFE DESIGN AND USE OF GAS PIPELINES - Rakhmonov Jobir Amanovich (Scholar Express Journals, 2024)
Natural gas is the mainstay of efficient and environmentally friendly energy. Indicators of rationality and efficiency of energy consumption - this is the energy efficiency of the house. These indicators are influenced by the economy of heating, lighting, water supply, ventilation, and what energyefficient materials and equipment were used in the construction of the house
Keywords: gas distribution system; gas distribution network; gas consumption network